2002
DOI: 10.1161/01.hyp.0000013863.25970.ba
|View full text |Cite
|
Sign up to set email alerts
|

Methoxyestradiols Mediate Estradiol-Induced Antimitogenesis in Human Aortic SMCs

Abstract: Abstract-Estrogen receptors (ERs) are considered to mediate the ability of 17␤-estradiol (estradiol) to reduce injury-induced proliferation of vascular smooth muscle cells (VSMCs), leading to vascular lesions. However, the finding that estradiol attenuates formation of vascular lesions in response to vascular injury in knockout mice that lack either ER-␣ or ER-␤ challenges this concept. Our hypothesis is that the local metabolism of estradiol to methoxyestradiols, metabolites of estradiol with little affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 26 publications
(27 reference statements)
4
58
0
1
Order By: Relevance
“…8 ER␣ and ER␤ expression were analyzed by Western blots. 9 Experiments were conducted in triplicate (repeated 3 or 4 times). Results are expressed as meanϮSEM.…”
Section: Methodsmentioning
confidence: 99%
“…8 ER␣ and ER␤ expression were analyzed by Western blots. 9 Experiments were conducted in triplicate (repeated 3 or 4 times). Results are expressed as meanϮSEM.…”
Section: Methodsmentioning
confidence: 99%
“…27 In addition to these actions on the vascular tonus, estrogen exerts an antiproliferative action on the vascular smooth layer. 48 Also, it appears to have a major role in vascular remodeling, inhibiting the proliferation of the inner layer after injury 49 and increasing the expression of contractile proteins in the myocardium. 50 In other tissues, such as the liver, estrogen can mediate both beneficial (expression of genes of apoproteins that improve the lipid profile) and adverse effects (increase in the expression of procoagulant factors and decrease of fibrinolytic factors).…”
Section: Estrogen Menopause and Endothelial Functionmentioning
confidence: 99%
“…Mori et al reported that the estradiol was protective against neointimal proliferation in female rats subjected to balloon dilatation of the carotids. 26 In addition, Dubey et al have reported that estradiol and some of its metabolites are antimitogenic in human aortic smooth muscle cells, 27 mesangial cells, 28 and cardiac fibroblasts. 29 Estradioleluting stents are now available and are being used in clinical trials in humans 30 to determine whether the estradiol-eluting stents are successful in protecting against neointimal proliferation.…”
Section: Estrogen: "Good Girl"mentioning
confidence: 99%